Chemical Properties of Buriganga and Turag River Water (Journal of Environmental Science and Natural Resources, 2017)
The present study was undertaken to evaluate the chemical properties of Buriganga and Turag river water, Bangladesh. Water samples were collected from 15 locations of each river from January to February, 2016 to analyze chemical properties, which includes: pH, EC, TDS, DO, cations ( Na+, K+, Ca2+, Mg2+), Anions (Cl-, HCO3-, SO42-, CO3-, PO43-) and heavy metal contents (Pb, Cd, Ni, Cr, As, Zn, Cu). The average value of pH was 8.47 and 8.41 in Buriganga and Turag water indicating moderate alkalinity. The average values of EC content of Buriganga and Turag river water were 327 and 272 ?S cm-1 indicating low to moderate salinity. The mean values of TDS and DO content were 1468.4 and 2.93 mg L-1 in Buriganga river water and 1202 and 3.91 mg L-1 in Turag river water, respectively. Average concentration of Pb, Cd, Ni, Cr, As, Zn, and Cu found in Buriganga and Turag river water were 0.068, 0.016, 0.081, 0.237, 0.006, 0.473, 0.19 mg L-1 and 0.012, 0.021, 0.015, 0.034, 0.002, 0.075, 0.014 mg L-1, respectively. From the study it is found that the value of Pb, Cd and Cr content in Buriganga and Cr content in Turag river water exceeded the standard limits of DoE and WHO. Therefore, Government and local people should take some effective measures to control the pollution of Buriganga and Turag river.J. Environ. Sci. & Natural Resources, 9(2): 9-14 2016